EFFECTS OF POST-IMPLEMENTATION COMMUNITY PARTICIPATION ON SUSTAINABILITY OF BOREHOLE WATER PROJECTS IN EMBU COUNTY, KENYA - Omanwa, Erick Bwoma; Muchai, Serah Kimaru (International Journal of Entrepreneurship and Project Management, 2021)
Purpose: The study sought to establish the effect of post-implementation community participation on sustainability of borehole water projects in Mbeere South sub county, Embu County. Methodology: The study employed cross-sectional research design. The target population comprised of 770 executive borehole management committee members, 16,800 household borehole water users in Mbeere South Sub County, five project managers from non-state agencies involved in rural water provision and management and two government water officers. The study used utilized a sample size of 657. Krejcie and Morgan table was used to select 260 executive borehole committee members while Yamane formula was employed to sample 390 household borehole water users who were selected from the five wards in Mbeere south sub county by use of proportionate random sampling method. Census sampling was applied to select two government water officers and five project officers from non-state agencies. The study used questionnaires and interview guides to gather primary data from the respondents. The questionnaires were piloted with 70 randomly picked respondents drawn from the target population to ascertain their reliability in gathering relevant data while content validity was achieved through review by experts and professionals in the field of study. Data analysis employed descriptive statistics using Statistical Package for Social Sciences (SPSS) Findings: Pearson Chi-Square analysis revealed that monitoring cases of vandalism and poor hand pump handling, monitoring hand pump defects and breakdowns, supervision of community-led maintenance and repair were statistically significant at 5% precision level with P- values of 0.000, 0.000, 0.020 respectively. The study also established that community caretakers technical training, availability of hand pump spare parts and technician entrepreneurs in village markets were statistically significant at 5% precision level with P-value of 0.000. In regard to financial transparency and accountability, beneficiaries' willingness to pay for water, availability of enough funds to cover maintenance and management costs, community demand for water, application of book keeping skills in borehole projects management and keeping of financial records of household payments were statistically significant at 5% precision level with P-value of 0.000, 0.006, 0.000, 0.000, 0.000 respectively. Further, 78.9% of the household water users indicated that there were no mechanisms for auditing the records prepared by the borehole management committees and regarding their involvement in financial decision making only 26.2% affirmed participation in financial decision-making process. Unique contribution to theory, practice and policy: The study recommends that community beneficiaries should be sufficiently mobilized and prepared to facilitate effective community management of rural borehole water projects during the post-implementation period as postulated by the Community Coalition Action and Citizen Participation theories. Additionally, the borehole management committees should be supported by external stakeholders to enhance their technical and financial management skills in order to ensure technical and financial sustainability of rural community managed borehole projects through facilitative and village-level operation and maintenance and effective accountability and transparency mechanisms.